Olanzapine associated heart block in weight‐restored anorexia nervosa. Issue 4 (10th August 2015) - Alwazeer, Ahmed; Hussain, Arif; Hickey, Anita; MacLean, David
<x xml:space="preserve">Abstract</x> Anorexia nervosa is a serious psychiatric disorder but the search for disease‐modifying biological agents have yielded few options. This case describes the efficacious use of olanzapine off‐label in weight restoration in an adolescent. However, occurrence of first‐degree heart block during treatment flags up a need for cardiac monitoring with such treatment across this age group.